A Re-evaluation of Discarded Deceased Donor Kidneys in the UK: Are Usable Organs Still Being Discarded?. Issue 7 (July 2017) - Mittal, Shruti; Adamusiak, Anna; Horsfield, Catherine; Loukopoulos, Ioannis; Karydis, Nikolaos; Kessaris, Nicos; Drage, Martin; Olsburgh, Jonathon; Watson, Christopher JE; Callaghan, Chris J.
Abstract : Background: A significant proportion of procured deceased donor kidneys are subsequently discarded. The UK Kidney Fast-Track Scheme (KFTS) was introduced in 2012, enabling kidneys at risk of discard to be simultaneously offered to participating centers. We undertook an analysis of discarded kidneys to determine if unnecessary organ discard was still occurring since the KFTS was introduced. Methods: Between April and June 2015, senior surgeons independently inspected 31 consecutive discarded kidneys from throughout the United Kingdom. All kidneys were biopsied. Organs were categorized as usable, possibly usable pending histology, or not usable for implantation. After histology reports were available, final assessments of usability were made. Results: There were 19 donors (6 donations after brain death, 13 donations after circulatory death), with a median (range) donor age of 67 (29-83) years and Kidney Donor Profile Index of 93 (19-100). Reasons for discard were variable. Only 3 discarded kidneys had not entered the KFTS. After initial assessment postdiscard, 11 kidneys were assessed as usable, with 9 kidneys thought to be possibly usable. Consideration of histological data reduced the number of kidneys thought usable to 10 (10/31; 32%). Conclusions: The KFTS scheme is successfully identifying organs at high risk of discard, though potentially transplantable organs are still being discarded. Analyses of discarded organs are essential to identify barriers to organ utilization and develop strategies to reduce unnecessary discard. Abstract : Due to organ shortage, kidney discarded rate must be minimized. The authors retrospectively evaluate the UK Kidney Fast-Track Scheme aiming at reducing unnecessary kidney discarding through sharing informations and better understanding this often obscure process.